Morphological abnormalities in gall‐forming aphids in a radiation‐contaminated area near Fukushima Daiichi: selective impact of fallout?. Issue 4 (13th January 2014) - Akimoto, Shin‐ichi
Abstract To evaluate the impact of fallout from the Fukushima Daiichi Nuclear Power Plant accident on organisms, this study compared the morphology and viability of gall‐forming aphids between the Fukushima population and control populations from noncontaminated areas. This study, in particular, focused on the morphology of first‐instar gall formers derived from the first sexual reproduction after the accident. Of 164 first instars from Tetraneura sorini galls collected 32 km from Fukushima Daiichi in spring 2012, 13.2% exhibited morphological abnormalities, including four conspicuously malformed individuals (2.4%). In contrast, in seven control areas, first instars with abnormal morphology accounted for 0.0–5.1% (on average, 3.8%). The proportions of abnormalities and mortality were significantly higher in Fukushima than in the control areas. Similarly, of 134 first instars from T. nigriabdominalis galls, 5.9% exhibited morphological abnormalities, with one highly malformed individual. However, of 543 second‐generation larvae produced in T. sorini galls, only 0.37% had abnormalities, suggesting that abnormalities found in the first generation were not inherited by the next generation. Although investigation is limited to one study site, this result suggests that radioactive contamination had deleterious effects on embryogenesis in eggs deposited on the bark surface, but a negligible influence on the second generation produced in closed galls. Furthermore, analysis of both species samples collected in spring 2013 indicated that the viability and healthiness of the aphids were significantly improved compared to those in the 2012 samples. Thus, the results of this study suggest the possibility that a reduced level of radiation and/or selection for radiation tolerance may have led to the improved viability and healthiness of the Fukushima population.